Egalitarian redistribution in the era of hyper-globalization. Issue 2 (2nd April 2020) - Grimalda, Gianluca; Trannoy, Alain; Filgueira, Fernando; Moene, Karl Ove
Abstract : Two traditional theorems of welfare economics posit a trade-off between a government redistribution targets and efficiency. We propose a third 'claim' of welfare economics, stating that in closed economies the actual efficiency costs associated with redistribution are small. We then examine the claim in the current phase of 'hyper-globalization'. On the one hand, a race-to-the-bottom in taxation restricts the capacity to tax high-earners and the associated brain drain may affect a country's long-run growth. On the other hand, demand for social insurance should be particularly high in an open economy, especially with advancing digitalization. Xenophobic sentiments may, however, offset this demand. We also discuss the impact of globalization on wage equalization and productive efficiency. We conclude against the idea that the welfare state is intrinsically unable to carry out its redistributive function in an era of globalization. However, its strategies and tools of intervention must be rethought.